PENERAPAN PENDEKATAN COMMUNICATIVE LANGUAGE TEACHING (CLT) PADA PEMBELAJARAN BAHASA ARAB DI DAYAH RAUDHATUL QUR’AN ACEH BESAR - Zikrullah Nuzuli, Zikrulah Nuzuli (Jurnal Cakrawala, 2023)
This study aims to describe the application of the Communicative Language Teaching (CLT) approach in Arabic language learning at Dayah Raudhatul Qur'an, Gampong Tungkop, Aceh Besar. The CLT approach was chosen because it is oriented towards developing the communicative competence of students through various meaningful language activities. This study uses a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation. The results show that Arabic teachers apply CLT principles through various activities such as paired dialogues, language games, contextual question and answer sessions, group work, and the use of authentic materials. These activities have been proven to increase students' courage in speaking, enrich their vocabulary, and encourage the active use of Arabic in learning situations. However, the application of CLT still faces a number of obstacles, including differences in students' basic abilities, limited supporting facilities, and the strong tradition of grammar-based learning that has long been used. Based on these findings, the application of CLT is considered quite effective in improving students' communicative skills, but it requires support in terms of facilities, teacher